Urban food forestry networks and Urban Living Labs articulations. Issue Volume 14:Issues 3(2021) (3rd July 2021) - Ribeiro, Barbara; Lewis, Nick
ABSTRACT: This article wrestles with the theoretical complexity of fostering food sustainability transitions in metropoles. It pays attention to how urban food forestry networks cultivated in parks may represent a critical part of these transitions, by providing a mechanism for urban peoples to reconnect with food processes while enhancing biodiversity and ecosystem services. The work considers this crucial topic, both theoretically and empirically, in two steps. First, a brief overview of utopian models and the critical literature grounds the discussion of the proposed regenerative place-making model. Second, the work weaves considerations regarding a utopian model of urban food forestry network, by conceptualising Urban Living Labs (ULLs) as flexible nodes of articulation. The work concludes that the key to unlocking this model's potential for replication and transplantation to distinct localities lies as much in the multiple values entailed by the proposed intervention as it does in its flexible nodes of articulation.